(untitled) (Sinología hispánica. China Studies Review, 2023)
A large number of Chinese literary works have been translated into Spanish and entered the Spanish market. Considering the differences between Chinese and Spanish languages and cultures, it is imperative to establish a model of criticism applicable to Chinese-Spanish translations. Therefore, in this article we studied significant proposals in the West (principally in Spanish-speaking countries) and in China to establish a new structure for translation criticism. Furthermore, we choose the homosexual texts in Jin Ping Mei as the object of analysis, and verify the feasibility of this critical paradigm from the linguistic (semantic and syntactic, rhetorical and stylistic), extra-linguistic (cultural and philosophical), and pragmatic perspectives, in order to determine a relatively objective textual norm and value standard.